Analysis of User Satisfaction with the DANA Digital Wallet Application in Lhokseumawe City Using the End-User Computing Satisfaction (EUCS) Method - F Saragih, Annisa; Muthmainnah, Muthmainnah; Ilhadi, Veri (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2025)
DANA is one of the most popular digital wallets in Indonesia. In accordance with the survei results in Lhokseumawe City, it was recorded that the number of DANA users was greater than other digital wallets. Therefore, researchers evaluate the level of satisfaction of DANA application users in the city and identify the factors that influence it using the EUCS method. EUCS is a technique for assessing the comparison between expectations and reality of an information system application to determine the level of user satisfaction with five independent variables, namely content, accuracy, format, ease of use, and timeliness, and the dependent variable is user satisfaction. The population of this research is people who live in Lhokseumawe City, with a sample of 349 respondents collected through questionnaires. From the results of data analysis using SPSS, four variables were found to affect the satisfaction of DANA digital wallet users in Lhokseumawe City, namely the content variable, format, ease of use, and timeliness. However, there is one variable that has no effect, namely the accuracy variable. However, there is one variable that has no effect, namely the accuracy variable. Based on the results of the analysis of the level of user satisfaction, the average number of overall user satisfaction level values on each variable is 3.984 and is included in the satisfied category, so it can be concluded that users are satisfied in using the DANA digital wallet application